(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Today, the educational system in the Philippines has changed because of the COVID-19 virus pandemic. The changes have affected all aspects, particularly education. Both private and public institutions are not allowed to report in school regularly because of the Health Protocol procedures implemented by the IAFT. Online Distance Learning or Blended learning is used for the learning modality of the institution in the Philippines. Both private and public schools from Basic Education, TESDA, and CHED were implemented to protect the teaching and non-teaching staff and students. In this situation, other schools will think about addressing the teachers’ needs, particularly the students’ information. In this regard, the researcher will conduct a study and develop a system to support the needs of the teachers, particularly the student’s information. Since the issues exist, the researchers will develop a faculty information system to have records and store the information of the teachers and students. The faculty information system keeps track of all the records of the teachers and even the students to lessen the printer papers as other problems to protect and maintain the environment. During the planning phase, the researchers brainstormed a brief system history. During the analysis phase, the researchers analyzed and processed the information data and records the teacher possessed. The convenient process has been completed during the design phase. The changing process is completed during the development phase. After checking, the researchers check the system to see if it works properly and fix any minor bugs before releasing it. The researchers released the system to Bestlink College of the Philippines, held a seminar for those users on how to use it and install our system on their devicess, and then implemented it. If the user encounters anomalies, the maintenance phase will be initiated; the user must contact the programmer for maintenance service.